Explicit two-dimensional solutions for the ocean flow in arctic gyres - Susanna V. Haziot (Faculty of Mathematics, University of Vienna) (Monatshefte für Mathematik, 2018)
The abstract is available here: https://uscholar.univie.ac.at/o:937286 The abstract is available here: https://uscholar.univie.ac.at/o:937286